Connectivity in the technology transfer process among local ASEAN firms - Masatsugu Tsuji; Hiroki Idota; Yasushi Ueki; Hidenori Shigeno; Teruyuki Bunno (Contemporary Economics, 2016)
This study focuses on the role of human factors in the innovation processes of firms in four member states of the Association of Southeast Asian Nations (ASEAN), i.e., Indonesia, Thailand, the Philippines, and Vietnam. Firms are required first to obtain new information related to innovation and then to integrate it with their indigenous resources. The innovation process thus consists of the absorptive process, through which outside information is employed to enhance innovation capability, and the transforming process, through which innovation capability creates innovation. This study identifies essential factors that promote these capabilities. In the absorptive process, two types of personnel are examined, i.e., employees who have experience working with multinational companies (MNCs) and those indigenous to the firm. As for the transforming capability, organizational learning processes, including quality control (QC) and cross-functional teams, are examined. Mail surveys were conducted from 2013 to 2014, and the total number of samples was 665. Based on the data, structural equation modeling (SEM) is employed. The analysis demonstrates that MNCs have the largest impact as external linkages. The most important mediators for locals to connect with MNCs are top management and factory managers who have experience working with MNCs, whereas indigenous employees, such as local engineers, managers, and line leaders, are identified for connectivity with locals. The direct and indirect effects of external linkages on innovation are also estimated. In the transforming process, cross-functional teams have a larger impact on innovation than QC
Keywords: O32; O31; O19; 330; absorptive capability; transforming process; organizational learning; cross-functional team; indigeneity